2019
DOI: 10.1177/1747954119887722
|View full text |Cite
|
Sign up to set email alerts
|

Shooting efficiency and structure of shooting in 3 × 3 basketball compared to 5v5 basketball

Abstract: This article presents and analyses certain playing characteristics of men's and women's 3 × 3 basketball in relation to shooting at the basket. Our intention was to compare this young and developing basketball discipline with the more established and traditional 5v5 basketball. For this purpose, over 400 matches were analysed in the U18 age category during the men’s and women’s European Championship (5v5 Basketball) and the Youth Olympic Games (3 × 3 Basketball). The research confirms some differences in the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 20 publications
6
40
0
Order By: Relevance
“…This finding may confirm recent research into elite youth 3 × 3 basketball which showed a greater number of inside shot attempts in comparison to outside shots, however the difference was not significant making findings unclear. 8 Anecdotally, players in this study reported that as they experienced fatigue in the latter stages of gameplay, they resorted to taking risky shots from further away from the basket rather than driving towards the rim for a layup. This approach may conserve energy as driving to the rim tends to result in a high level of contact from either one or two opponents.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…This finding may confirm recent research into elite youth 3 × 3 basketball which showed a greater number of inside shot attempts in comparison to outside shots, however the difference was not significant making findings unclear. 8 Anecdotally, players in this study reported that as they experienced fatigue in the latter stages of gameplay, they resorted to taking risky shots from further away from the basket rather than driving towards the rim for a layup. This approach may conserve energy as driving to the rim tends to result in a high level of contact from either one or two opponents.…”
Section: Discussionmentioning
confidence: 83%
“…9,10 Similarly, during the 2017 3 × 3 World Cup, free throws, turnovers and recovered balls per possession were demonstrated to be the main game-related statistics discriminating between winning and losing teams. 7 More recently, Erčulj et al., 8 demonstrated a trend towards close-range shots being taken more frequently than long-range shots in elite youth 3 × 3 players, however the difference was non-significant. Physiologically, during 3 × 3 basketball, males and females exhibit mean game heart rates of 164 ± 12 beats per minute (bpm −1 ) and 165 ± 18 bpm −1 , and mean blood lactate levels of 6.33 ± 2.43 and 6.09 ± 2.24 mmol⋅L −1 , respectively (mean±SD).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Basketball is considered a unique sport because it is created accidentally by a priest (González-Espinosa et al, 2021;Moore et al, 2021). In 1891, Dr. James A. Naismith a Canadian pastor who teaches on a faculty for professional students at the YMCA (Young Men's Christian Association) a Christian youth organization, in Springfield, Massachusetts, must make games in a closed room to fill students' time during the holidays winter in New England (Erčulj et al, 2020;Montgomery et al, 2021). Because it is done indoors or in a building, the idea arises that the game should be a game that is not too rough, with no kicking elements, and tackles, interesting, and not too difficult to learn (Meisel et al, 2022;Ott & Santos, 2020).…”
Section: T Testmentioning
confidence: 99%